Combining Models of Root-Zone Hydrology and Geoelectrical Measurements: Recent Advances and Future Prospects - Mary, Benjamin; Peruzzo, Luca; Iván, Veronika; Facca, Enrico; Manoli, Gabriele; Putti, Mario; Camporese, Matteo; Wu, Yuxin; Cassiani, Giorgio (Frontiers in Water, 2021)
Recent advances in measuring and modelling root water uptake along with refined electrical petrophysical models may help fill the existing gap in hydrological root model parametrization. In this paper, we discuss the choices to be made to combine root-zone hydrology and geoelectrical data with the aim of characterizing the active root zone. For each model and observation type we discuss sources of uncertainty and how they are commonly addressed in a stochastic inversion framework. We point out different degrees of integration in the existing hydrogeophysical approaches to parametrize models of root-zone hydrology. This paper aims at giving emphasis to stochastic approaches, in particular to Data Assimilation (DA) schemes, that are generally identified as the best way to combine geoelectrical data with Root Water Uptake (RWU) models. In addition, the study points out two pathways for improvement of geoelectrical data integration into RWU models using DA.